Analisis Faktor Demotivasi Mahasiswa dalam Mendalami Bahasa Arab : Studi Kasus Mahasiswa Pendidikan Bahasa Arab Universitas Islam Negeri Sumatra Utara) - Huwaina Rabithah Nur; Salwa Haifa; Kiki Haura Shandi; Sahkholid Nasution (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The problem behind this research is the decline in motivation in studying Arabic among PBA students in 2021 UINSU. The purpose of this research is to find out what factors are behind demotivation in studying Arabic among PBA 2 students of Stambuk 2021 UINSU. This research hopes to perfect previous studies and so that educators can develop strategies in reviving the motivation of Arabic language learners. The method used in this research is a qualitative method. The data collection technique is by conducting observations and interviews with PBA 2 students of 2021 UINSU. The data collected were then analyzed and grouped based on the similarity of the informants' answer patterns. The results of this study indicate that the factors behind student demotivation in studying Arabic are; First. The burden of the Academy. Second; Learning Methods. Third; Arabic language complexity. Fourth; Not having a language environment. Fifth. Teacher's personality. Sixth. Economic Factors.